SVep1, a temperate phage of human oral commensal Streptococcus vestibularis - Wu, Miaomiao; Zhu, Yanpeng; Yang, Yuhui; Gong, Yali; Chen, Zongyue; Liao, Binyou; Xiong, Yu; Zhou, Xia; Li, Yan (Frontiers in Microbiology, 2023)
Bacteriophages play a vital role in the human oral microbiome, yet their precise impact on bacterial physiology and microbial communities remains relatively understudied due to the limited isolation and characterization of oral phages. This study aimed to isolate and characterize novel oral phages. Oral bacteria were isolated using a culture-omics method from 30 samples collected from healthy individuals. After culturing the bacteria in three media types under both aerobic and anaerobic conditions, full-length 16S rRNA gene sequencing was performed. 75 bacterial strains were successfully isolated, representing 30 species and 9 genera, with Streptococcus having the highest species count. Using a 16S rRNA similarity threshold of 98.65%, 14 potential novel bacterial species were identified. Next, a temperate phage targeting the human oral commensal bacterium S. vestibularis strain SVE8 was isolated. S. vestibularis SVE8 has a 1.96-megabase chromosome and a 43,492-base pair prophage designated as SVep1. SVep1's annotation revealed 62 open reading frames, mostly associated with phage functions. However, when S. vestibularis SVE8 was re-infected with lysogenic phage obtained by mitomycin C treatment, no plaques were observed on the double layer agar. Phage particles were successfully isolated from the supernatant of mitomycin C-treated cultures of S. vestibularis SVE8, and transmission electron microscopy confirmed SVep1 as a siphovirus. Phylogenetic analysis suggested a common ancestral origin between phage SVep1 and the cos-type phages found in S. thermophilus.